THE IMPACT OF DEMOGRAPHIC CHANGES ON THE LABOR MARKET IN ALGERIA PROSPECTS FOR 2050 - Rima Merrad; Karima Fouded (International Journal of Innovative Technologies in Social Science, 2025)
The changes that population societies are witnessing due to the pressures caused by demographic growth and transformations in economic conditions, and the necessity to adapt to them, require a series of measures and actions aimed at solving the problems arising from this situation. These problems become impossible to address without the existence of data and statistics related to the population in general and the workforce in particular. Improving the quality of this data and providing it regularly is essential for policy planning and setting future strategies through demographic forecasts. Population projections are not limited to the demographic aspect only; every institution is obliged to take into account the various demographic changes that could affect its activities. Undoubtedly, the current situation in Algeria amidst global transformations compels it to take measures and actions that allow it to plan its policies, especially with the increase in first-time job seekers. Our research paper aims to monitor the impact of demographic changes on the labor market in Algeria.